2016
DOI: 10.3390/nu8030139
|View full text |Cite
|
Sign up to set email alerts
|

Median Urinary Iodine Concentrations Are Indicative of Adequate Iodine Status among Women of Reproductive Age in Prey Veng, Cambodia

Abstract: Iodine deficiency disorders are estimated to affect over 1.9 million people worldwide. Iodine deficiency is especially serious for women during pregnancy and lactation because of the negative consequences for both mother and infant. The aim of this cross-sectional study was to determine the median urinary iodine concentration (UIC) as a population-level indicator of iodine status among rural women farmers of reproductive age (18–45 years) in the province of Prey Veng, Cambodia. A total of 450 women provided a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The results are similar to the NFCS-FB-1 of nonpregnant women in South Africa (median UIC of 176.8 μg/l), which reported adequate iodine nutrition. 17 In Cambodia, Karakochuk et al 20 also found adequate iodine status in pregnant women. The results of our study, however, showed that there was variation in median UICs when measured in different trimesters.…”
Section: Tsh Levels Of Pregnant Womenmentioning
confidence: 95%
“…The results are similar to the NFCS-FB-1 of nonpregnant women in South Africa (median UIC of 176.8 μg/l), which reported adequate iodine nutrition. 17 In Cambodia, Karakochuk et al 20 also found adequate iodine status in pregnant women. The results of our study, however, showed that there was variation in median UICs when measured in different trimesters.…”
Section: Tsh Levels Of Pregnant Womenmentioning
confidence: 95%
“…In school-age children and non-lactating or non-pregnant women, a median UIC range of 100-299 μg/L shows that iodine deficiency does not occur in a population with any more than 50% of urine samples below 100 μg/L and not more than 20% of samples should have an iodine concentration below 50 μg/L [26][27][28]. Kismantoro and Slogohimo sub-districts, Wonogiri Regency has no iodine deficiency, 10% of urine samples in of childbearing ages 100 μg/L and 2.9% of urine samples below 50 μg/L (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In some iodine excess areas, the median UIC of more than 1000 μg/L has been reported [23]. Similarly, a review article on Cambodian school‐aged children's iodine status showed median UIC levels between 200 and 299 μg/L, indicating more than adequate iodine status [24]. Another Chinese study reported iodine excess with a median UIC of 750.18 μg/L [3].…”
Section: Discussionmentioning
confidence: 99%